Investigating the effect of accelerating/decelerating motion of a moving mass on the out-of-plane dynamics of horizontally curved beams - M.A. Foyouzat; H. Abdoos; A.R. Khaloo (مهندسی عمران شریف)
Horizontally curved beams (HCBs) are not only capable of meeting some architectural and aesthetic requirements but can also offer structural advantages in many engineering applications. Due to inherent complexities existing in the treatment of the problems dealing with dynamic actions on HCBs, the dynamic behavior of such salient elements is not essentially well understood. Therefore, to address the identified gap concerning the motion-type effects of a moving mass on the dynamics of HCBs, the current study deals with assessing how the accelerating/decelerating conditions do contribute to the out-of-plane response of HCBs under the excitation of a moving mass. In this regard, the governing dynamic equations are developed by taking care of the centripetal force, Coriolis acceleration, and inertial actions of the moving mass. Employing the method of separation of variables and exercising sinusoidal modal functions, the discretized system of differential equations in the matrix form are distilled and solved through the application of standard numerical procedures. Spectral responses in terms of the out-of-plane displacement and bending moment are then obtained for various influential parameters. The veracity of the results is also validated against the available data addressed in the technical literature. Through a comprehensive parametric study, the effect of the key parameters, including the central subtended angle and length of the HCB, as well as the mass, initial velocity, and increasing/decreasing acceleration of the moving mass, is evaluated on the out-of-plane displacement and bending moment of the supporting HCB. The results of this study suggest that in the accelerating mode, the out-of-plane displacement and bending moment spectra are magnified up to 18.11 and 27.53 percent compared with the spectral values corresponding to the constant-velocity mode. On the other hand, in the decelerating condition, the out-of-plane displacement and bending moment spectra are respectively alleviated up to 41.59 and 42.05 percent.